Reading Disability in Indonesian Childrenâ€™s Literature - Sugiarto, Tri (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2020)
The purpose of this article is to examine the representation of disability and to identify thediscourse resulted from the pattern of its portrayal in four selected Indonesian childrenâ€™sshorts stories, namely â€œKacamata UFOâ€, â€œGadis Penariâ€, â€œBapak Si Donoâ€, and â€œCerita Riondengan Sebelah Mataâ€ published in Bobo magazine. Applying the lens of Saidâ€™s Orientalism,this content analysis study shows that children with disabilities are presented as weak,dependent, not productive, an object of curiosity and violence, and a vehicle for the growth ofother characters in the story. This study concludes that literacy on disability for Indonesianpeople is significant. Such writing is to provide a positive image and reduce the negativestereotype which is currently shared among society.Keywords: childrenâ€™s literature, disability, representation, short stories